MEKANISME, IMPLEMENTASI SERTA EVALUASI PEMUNGUTAN DAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KAPANEWON DEPOK - Binawati, Enita; Agustina, Henis; Affan, Junaidi; Suprihadi, Suprihadi; Agustiyani, Alief Indita (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose this intership activities to find out : (1) The mechanism in proses of collecting and payment land and building tax in Depok District. (2) Implementation of collection and payment of land and building tax to public or taxpayers in Depok District. (3) Evaluation of mechanism and implementation of collection and payment of land and building tax in Depok District. The method used in data collection in intership activity is the obsevation method, interview method, and documentation method. The results of intership activities show that : (1) The working mechanism is regulated in Sleman Regent’s Regulation and a simple mechanism carried out by village government to make it easier to public or taxpayers. (2) The implementation of activities that running well and in accordance with the objectives expected the local government, district and village government but there are still differences that need to be studied further by regional government, district and village government regarding the regulation for payment and deposit of land and building taxes in rural and urban areas. (3) The evaluation of the PBB payment week activities for 2022 went well and regulary, get a lot of enthusiasm from public or taxpayes in proses of collection and payment land and building tax